2007
DOI: 10.1108/03074350710739614
|View full text |Cite
|
Sign up to set email alerts
|

Initial performance of Greek IPOs, underwriter's reputation and oversubscription

Abstract: Purpose -This paper aims to provide additional international evidence on the initial public offerings (IPOs) by examining the initial performance and two main determinants of short-run underpricing of 169 IPOs listed on the Athens Stock Exchange (ASE) over the period 1997-2002. Design/methodology/approach -In the first stage, the initial performance of the IPOs is measured by two calculated formulas: the raw returns and the excess or adjusted returns of the first, fifth and 21st day, respectively. In the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 24 publications
4
32
1
1
Order By: Relevance
“…Variables are taken differently, so they shows the different results. Guner (2000) and Jones (2010) state that the underwriter factors are negative significant on initial return, supported by two other studies of Kenourgios (2007) and Sharma (2010) with prestige variable, and also by Fung (2008) that states that the underwriter ranking effects negatively. However, two other studies found that underwriter factors have no significant effect on initial return, proposed by Almeida (2011) and Su (2011).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Variables are taken differently, so they shows the different results. Guner (2000) and Jones (2010) state that the underwriter factors are negative significant on initial return, supported by two other studies of Kenourgios (2007) and Sharma (2010) with prestige variable, and also by Fung (2008) that states that the underwriter ranking effects negatively. However, two other studies found that underwriter factors have no significant effect on initial return, proposed by Almeida (2011) and Su (2011).…”
Section: Introductionsupporting
confidence: 59%
“…Aggarwal and Rivoli (1990) and Ritter (1991) in Durukan (2002) suggest that abnormal initial return is not because of systematic underpricing, but it is because of overvaluation by investors or the mode in the early aftermarket trading. Kenourgios (2007) also adds some points in the hypotheses that affect IPO underpricing, they are: 1. Monopsony power of underwriters hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the same principle and the formulae for the raw returns on stocks, the same methodology was utilized for the raw returns on the Market Index, as follows: (2) As Kenourgios et al (2007), Hensler et al (2000) data were adjusted for a possible change in market conditions causing an impact on the changes in the price. The estimation of excess of returns is calculated using the formula (3) which is calculated by subtracting the Market Index of the raw returns on stocks and the raw returns.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…Earlier research found that the underwriter's reputation affects the underpricing level (Kenourgios et al, 2007). Table 5 examines the underwriter's prestige and average underpricing.…”
Section: Underpricing By Underwriter's Prestigementioning
confidence: 99%